Locating fish bomb blasts in real-time using a networked acoustic system. (March 2018) - Showen, R.; Dunson, C.; Woodman, G.H.; Christopher, S.; Lim, T.; Wilson, S.C.
Abstract: Results are presented of a demonstration of real-time fish blast location in Sabah, Malaysia using a networked hydroacoustic array based on the ShotSpotter gunshot location system. A total of six acoustic sensors - some fixed and others mobile - were deployed at ranges from 1 to 9 km to detect signals from controlled test blasts. This allowed the blast locations to be determined to within 60 m accuracy, and for the calculated locations to be displayed on a map on designated internet-connected computers within 10 s. A smaller three-sensor system was then installed near Semporna in Eastern Sabah that determined the locations of uncontrolled blasts set off by local fishermen. The success of these demonstrations shows that existing technology can be used to protect reefs and permit more effective management of blast fishing activity through improved detection and enforcement measures and enhanced community engagement. Graphical abstract: Unlabelled Image Highlights: Networked underwater acoustic sensors can locate fish blasting in real-time. Excellent system accuracy and long range of sensors is demonstrated. Governments can now more readily suppress the practice of fish blasting.